From Data Assets to Value Creation: Competitive Advantage in the AI Age - Franklin Ore Areche; Silvia Hypatia Sarabia Cansaya; Daniela Laura (Bincang Sains dan Teknologi, 2025)
The rapid advancement of Artificial Intelligence (AI) has fundamentally transformed how organizations create and sustain competitive advantage. In contemporary business environments, data is no longer treated merely as a supporting asset but has emerged as a primary source of value creation. This article examines how data-driven approaches, enabled by AI technologies, generate competitive advantage through enhanced decision-making, personalization, and operational efficiency. Using a conceptual research method, this study synthesizes findings from international peer-reviewed journals to analyze the mechanisms through which data becomes economic value. The Results and Discussion section elaborates on three core dimensions: the transformation of data into value generators, the economic characteristics of data in AI-driven markets, and the strategic logic of value creation through data–algorithm–context alignment. The findings indicate that data-driven competitive advantage is contingent not only on data volume but also on data quality, governance, and organizational capability. This article contributes to the growing body of literature on AI-enabled strategy by offering an integrated framework for understanding data as a strategic source of competitive advantage.